THE EFFECT OF HUMAN RESOURCES DEVELOPMENT ON THE QUALITY OFINPATIENT MEDICAL RECORDSATSALEWANGANGHOSPITAL MAROS REGENCY - Ayu lestari, Sri; Palutturi, Sukri; Sirajuddin, Saifuddin (International Journal of Psychosocial Rehabilitation, 2020)
Quality medical record is one of the indicators in assessing the quality of health services in a hospital. This study aims to conduct in-depth research on the effect of the development of human resources (health workers) on the quality of the inpatient medical records at Salewangang Hospital Maros. This research was an analytical observational study with a cross-sectional study design. Sampling was conducted by non-probability sampling technique, while the sample size was determined using the Slovin’s formula. From the total population, a sample of 170 respondents consisting of doctors and nurses was obtained. In addition, there were 170 inpatient medical records as samples. The results of the analysis showed that there was no relationship between the knowledge and motivation of health workers and the quality of the medical records which included the completeness, the accuracy and the punctuality of returning medical records. Furthermore, there was no relationship between the work discipline of health workers (doctors) with the quality of the medical records which included the completeness, accuracy and punctuality of returning medical records. There was also no relationship between the work discipline of the health workers (nurses) with the completeness and the punctuality of returning the medical records. Last but not least, there was a relationship between the work discipline of the health workers (nurses) and the accuracy of the medical records. As a recommendation, the hospital should conduct regular socialization on the importance of the completeness and the accuracy in filling out the medical records files to improve the discipline of the health workers, especially the nurses.